STRATEGIES FOR REDUCING STUDY BEHAVIOUR PROBLEM OF REMEDIAL STUDENTS IN KANO METROPOLIS: COUNSELING PERSPECTIVE - Abdullahi, Mustapha Ibrahim (Sokoto Educational Review, 2020)
This paper examined the effectiveness of two study approaches (SQ3R and 2SNPECR) on reducing study behaviour problem of remedial students in higher institutions in Kano Metropolis. Two inventories namely Study Habits Inventory (SHI) and Self Assessment Study Inventory (SASI) were administered to 300 hundred students sampled from remedial students. ANCOVA and Schaeffer test statistical analyses were employed in data analysis and the results revealed that study behaviour problem can be reduced to the barest minimum using the two study counseling approaches. It further revealed that gender difference does not affect the treatment hence both male and female are capable of benefiting equally from the treatment package.